Using Mind Mapping to Improve Students' Ability in Writing Recount Text - Hayati Hayati; Adnan Latief; Emilia Iragiliati (Universitas Negeri Malang, 2015)
Abstract: This study was aimed to improve the students' ability in writing recount text through mind mapping strategy. The subjects of the study was the 20 second graders of SMPN 2 Lumbang Probo-linggo. This was a classroom action research conducted in one cycle that consisted of five meetings. The mind mapping strategy was done through process writing, in the first three stages, pre-writing, drafting, and revising. The findings showed that the use of mind mapping strategy could improve the students' abilities in writing recount text. It is recomended that the English teachers use the mind mapping strategy to improve their students' writing, and the future researchers are suggested to conduct further studies related to the use of mind mapping strategy. Key Words: writing skills, mind mapping, recount texts Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan siswa dalam menulis teks recount dengan strategi mind mapping. Subjek penelitian ini adalah 20 siswa kelas 2 di SMAN 2 Lumbang Probolinggo. Penelitian ini berupa penelitian tindakan kelas yang dilakukan dalam satu siklus dan terdiri dari lima pertemuan. Strategi mind mapping dilakukan dengan proses menulis melalui tiga ta-hap pertama yaitu; pra-menulis, penyusunan, dan merevisi. Temuan menunjukkan bahwa penggunaan strategi mind mapping dapat meningkatkan kemampuan siswa dalam menulis teks rekon. Disarankan bahwa guru Bahasa Inggris menggunakan strategi pemetaan pikiran untuk meningkatkan kemampuan menulis siswa mereka, dan para peneliti selanjutnya disarankan untuk melakukan penelitian lebih lanjut terkait dengan penggunaan strategi pemetaan pikiran. Kata kunci: keterampilan menulis, pemetaan pikiran, teks rekon